Computer Security - ESORICS 2008 13th European Symposium on Research in Computer Security, Málaga, Spain, October 6-8, 2008. Proceedings - Jajodia, Sushil (Security and Cryptology ;, 2008)
This book constitutes the refereed proceedings of the 13th European Symposium on Research in Computer Security, ESORICS 2008, held in Torremolinos, Spain, in October 2008. The 37 revised full papers presented were carefully reviewed and selected from 168 submissions. The papers are organized in topical sections on Intrusion Detection and Network Vulnerability Analysis; Network Security; Smart Cards and Identity management; Data and Applications Security; Privacy Enhancing Technologies; Anonymity and RFID Privacy; Access Control and Trust Negotiation; Information Flow and Non-transferability; Secure Electronic Voting and Web Applications Security; VoIP Security, Malware, and DRM; Formal Models and Cryptographic Protocols; Language-based and Hardware Security.